Digital Tools and the Flipped Classroom Approach in Primary Education - Loizou, Maria (Frontiers in Education, 2022)
This article is an expansion of an existing research on the Flipped Classroom (FC) approach, adopted in five different primary schools in Cyprus and considering the experiences and perceptions of five teachers and 77 students (Loizou and Lee, 2020). It particularly expands in exploring the digital tools effectively used to teach primary school students through a FC. The FC approach is an innovative initiative which promotes blended learning methodology. It involves the use of digital technologies for developing and sharing flips/tutorials on the content traditionally taught through lecturing in class. Diverse technology tools have been used in FC research together with online learning platforms. The video tutorials, a basic form of a flip, are usually made by the educators with narration, text and enriched with various annotations and images. Many FC studies have added to the list of essential digital tools for FC implementation, especially the ones which showcase how flips can be developed. However, most of them have not indicated how can these be used for younger students, focusing mainly only in secondary or higher education. For example, how can the structure of a virtual learning environment can be simplified or how can administration of online documents in Drives be more suitable for young ages are scarcely explained. Hence, the significance of this study lies on the fact that research on the FC approach in primary education and the digital tools supporting it, has been so far kept to the minimum. Therefore, by collecting the experiences and perceptions of those involved in the process and assessing how the digital tools may or may not promote a positive learning experience could give an indication in how FC can be effectively implemented in primary education. A qualitative research methodology has been adopted by interviewing the five teachers and forming 11 different focus groups of students. Following the transcription, NVivo11 had been used for the thematic analysis. Research results have shown that the most effective digital tools can be categorized into software supporting: 1) Flips; 2) Activities in class; 3) Communication; 4) Entrance tickets; 5) Collaboration; and, 6) Assessment. These tools, recognized as simple and useful by students and teachers, have guided the creation of the ‟FC Technology tool” which incorporates examples for each category. Overall, a clear illustration of the kind of technology that could be used both at home and in-class for effective FC implementation in primary education is given in the study. Future studies should further evaluate how students can use these tools in forming their own flips and/or tutorials and be part of the pre and in-class session of FC learning classes.